2013
DOI: 10.1007/s00264-013-1866-9
|View full text |Cite
|
Sign up to set email alerts
|

Patellar resurfacing versus nonresurfacing in total knee arthroplasty: A meta-analysis of randomised controlled trials

Abstract: Purpose Patella resurfacing or nonresurfacing in total knee arthroplasty remains controversial. The aim of this study was to evaluate the efficacy of patellar resurfacing through an evaluation of the current literature. Methods We carried out a meta-analysis of randomised controlled trials comparing total knee arthroplasties performed with and without patellar resurfacing. Outcomes of reoperation, anterior knee pain and knee scores were analysed. Results Fourteen trials assessing 1,725 knees were eligible. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 35 publications
(48 reference statements)
4
65
0
1
Order By: Relevance
“…In 2013, the randomized controlled trial by Pulavarti et al [47] shed more light on the subject of patellar denervation without resurfacing: the method appeared safe, and improved patient satisfaction and range of knee flexion but did not ameliorate validated knee scores in a followup of 2 years [45] . Finally, Chen et al [48] also in 2013, published a meta-analysis of randomized controlled trials which supported the point of view that patellar resurfacing reduced the risk of reoperation and, moreover, gave better results in Knee Society Score in a follow-up of 5 years or more, but the overall benefits of the method were not sufficient to convince the authors to prefer this method over patellar non-resurfacing [48] .…”
Section: No Differences Among Studied Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, the randomized controlled trial by Pulavarti et al [47] shed more light on the subject of patellar denervation without resurfacing: the method appeared safe, and improved patient satisfaction and range of knee flexion but did not ameliorate validated knee scores in a followup of 2 years [45] . Finally, Chen et al [48] also in 2013, published a meta-analysis of randomized controlled trials which supported the point of view that patellar resurfacing reduced the risk of reoperation and, moreover, gave better results in Knee Society Score in a follow-up of 5 years or more, but the overall benefits of the method were not sufficient to convince the authors to prefer this method over patellar non-resurfacing [48] .…”
Section: No Differences Among Studied Groupsmentioning
confidence: 99%
“…Chen et al [48] Meta-analysis of randomized controlled trials Patellar resurfacing vs nonresurfacing in primary TKR Patellar resurfacing reduces the risk of reoperation after TKR. No difference between the 2 groups in terms of anterior knee pain, knee pain score, Knee Society score and knee function score Pilling et al [44] Meta-analysis of randomized controlled trials.…”
Section: Ref Type Of Study Outcomementioning
confidence: 99%
“…While some studies and meta-analysis have shown patella resurfacing to be better in terms of cost-effectiveness, reduced revision rate for anterior knee pain, and produced less anterior knee pain, emerging evidence suggests that resurfacing has no influence on the clinical outcome of the patient. [12][13][14][15][16][17] Proponents of retention of the native patella claim that it has no affect on total healthcare cost, reoperation rate or functional outcome and has a lower complication rate. [18][19][20][21] TKA is one of the most commonly performed operations in adult reconstructive surgery and there currently exists three different approaches among orthopedic surgeons regarding patellar resurfacing: resurfacing all patellae, not resurfacing all patellae, and selective resurfacing for patients with significant pre-operative patellofemoral arthritis-related symptoms and/or advanced patellofemoral arthritis on radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…Anterior knee pain (AKP) is observed in TKA both with and without patellar resurfacing (5,6,8,9). Neither patellar denervation (4,10) nor secondary resurfacing (11,12) proved effective for treating the symptoms.…”
Section: Introductionmentioning
confidence: 99%